Learning Styles and Academic Achievement in College Students from Buenos Aires - Freiberg Hoffmann, Agustín (2015)
Learning styles analyze cognitive-intellectual aspects participating in every learning situation (Curry, 1983). The study describes the behavior of this concept in 300 college students of various degree courses (Biology, Industrial Engineering, Law, Nutrition, Psychology, and History of Art). Goals aimed at the analysis of learning styles according to personal and academic variables-gender, age, major and academic achievement, as well as the assessment of each style?s ability to predict the students? achievement. Results showed a general medium preference for every style in students of every degree course. Pragmatist style was manifested in males and in younger students. Converging style was remarkable in Engineering, as well as Nutrition and Biology students, compared to Psychology and History of Art. Analyzing styles by academic achievement, significant differences in Assimilating and Converging types were verified in Biology high-achievers. Finally, academic achievement was explained by a regression model where every learning style participates as a predictor. Results are discussed on a theoretical basis as well as considering practical outcomes. Keywords: academic achievement, CHAEA, college students, Kolb, learning styles